What we need from our families the perspective of male and female adolescents with cancer - Sumpaico, Nina Nerissa J. (2012)
This exploratory study describes the perspective of male and female Adolescents with Cancer (AWC), which focuses on: (1) their understanding of cancer, (2) needs from the family, (3) ways that family responds to needs and (4) communication patterns between AWC and their families. Eleven male and nine female adolescents with various types of cancer, between 13 and 19 years old participated in the study. Seven focus group discussions (FGD) were conducted with these AWC in selected hospitals within Metro Manila. Non-probability sampling was done through purposeful selection. General themes were generated from the FGD, to define the perspective of male and female AWC. Results show that cancer frames the development of AWC. Their understanding of cancer includes physical, emotional, cognitive and social components, which determine what AWC need from their families. Central to these needs is family support experienced in various ways, whether physical, material or emotional. Fulfillment of needs occurs in varying degrees, depending on individual experiences. Gender differences were found between the male and female AWC perspective, which relate to the distinct ways daughters and sons are treated and raised in the Filipino family. Male and female AWC also share many common views, which can be attributed to their common experience of cancer. Findings of the study can lead to future studies that can further the body of knowledge available on adolescent cancer. Programs can also be developed that can help provide better quality of care and quality of life for AWC and their families.